Sistem Pakar Berbasis Web Untuk Analisa Stress Sebelum Presentasi Kerja - Rina Noviana; Lely Prananingrum; Budi Utami Fahnun (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2012)
Expert System Application for stress analysis in the face of the presentation of work which is an expert system application that can be used to help users minimize risks of bad possibilities that can happen during a presentation in front of the audience crowd. In making this application of this expert system, using software PHP, MySQL. Software used in the making of this application using PHP because PHP is a programming language that is open source means anyone can use it and not blocked, while MySQL is a database management system software data (Data Base Management System) that is easy to learn in making resource Data and data processing.Keywords: Expert System, PHP, MySQL.